PENGARUH EKSTRAK ETANOL KULIT BUAH MANGGIS DAN DAUN PEPAYA TERHADAP KADAR BILIRUBIN PADA TIKUS PUTIH YANG DIINDUKSI ISONIAZID DAN RIFAMPISIN - Meta Kartika Untari; Yane Dila Keswara; Nur Aini Dewi Purnamasari (Jurnal Farmasi Indonesia, 2015)
Tuberculosis (TB) is a disease with a very high prevalence in Indonesia. Clinical trials of drugs isoniazid and rifampicin have known most active in combating tuberculosis in the lungs. Side effects caused by administration of OAD (anti-tuberculosis drugs) one of them is a liver function disorders characterized by elevated levels of serum bilirubin. This study aimed to determine the activity of a decrease in serum bilirubin levels in rats induced after administration of isoniazid and rifampin combination of ethanol extract of mangosteen peel and papaya leaf. Serum bilirubin measurement method using a spectrophotometer, the bilirubin level is expressed in mg / dl. Data were analyzed using Kruskal-Wallis method shows that there was a significant difference between the treatment groups (p <0.05), while between the time measurements showed no significant difference. A combination of ethanol extract of papaya dose of 120 mg / 200 g BW rat, and the ethanol extract of mangosteen peel dose of 160 mg / 200 g rat BW the most effective of all treatment groups in lowering levels of bilirubin in isoniazid and rifampicin induced rat.